Does Emotional Intelligence and Self-Efficacy Predict Transformational Leadership in Law Enforcement Managers: A Quantitative Study - John Walsh, DM (The Pinnacle)
This study examined the predictive relationship between emotional intelligence, self-efficacy, and transformational leadership in law enforcement management. While transformational leadership is widely recognized for enhancing organizational success and employee well-being, research often focuses on corporate settings, overlooking the unique challenges of law enforcement. Additionally, emotional intelligence and self-efficacy are frequently studied in isolation, leaving gaps in understanding their combined influence on leadership in high-stress environments. Using quantitative correlational design, data was collected from 82 law enforcement managers in Southwest Florida through validated instruments: the Wong and Law Emotional Intelligence Scale, Leader Efficacy Questionnaire, and Multifactor Leadership Questionnaire. Multiple regression analysis assessed the predictive contributions of emotional intelligence and self-efficacy, while Spearman’s correlation examined their relationships.